The QTc Effect of Low‐Dose Methadone for Chronic Pain: A Prospective Pilot Study. Issue 6 (3rd February 2015) - Grodofsky, Samuel; Edson, Emmanuel; Huang, Stephanie; Speck, Rebecca M.; Hatchimonji, Justin; Lacy, Kim; Farrar, John T.; Ashburn, Michael A.
Abstract Objective Methadone is associated with QT prolongation and serious cardiac complications, but this has been primarily demonstrated in opioid dependent patients receiving moderate to high doses. This study investigates the effect of low‐dose methadone on the QTc interval in a chronic pain population. Design and Subjects We conducted a prospective cohort study in a chronic pain clinic including 82 patients receiving methadone and 102 patients receiving non‐methadone opioid therapy. Methods We analyzed automated QTc calculations from 12‐lead electrocardiograms at baseline and during the subsequent 6 months. The primary outcome of interest was the incidence of QTc greater than 470 milliseconds or an increase from baseline of greater than 60 milliseconds. Results The methadone group did not manifest an overall higher frequency of QTc > 470 milliseconds (6% for the methadone group vs 5% for controls, P = 0.722) or an increase in the QTc of > 60 milliseconds (4% for the methadone group vs 4% for controls, P = 0.94). In the first month after initiating methadone, patients demonstrated an increase in QTc compared to controls (5% for the methadone group vs 0% for the controls, P = 0.073) but the difference disappeared in the third and sixth months. Conclusion Data from our chronic pain clinic support a potential association of QTc prolongation during the initiation of methadone, but this effect is small and short lived. We believe larger scale studies to further characterize the safety profile of low‐dose methadone are warranted.